Thermotherapy Effective and Safer than Miltefosine in the Treatment of Cutaneous Leishmaniasis in Colombia (2013)
ABSTRACT: In Colombia, pentavalent antimonials and miltefosine are the drugs of choice for the treatment of cutaneous leishmaniasis; however, their toxicity, treatment duration, (treatment adherence problems), cost, and decreased parasite sensitivity make the search for alternative treatments of American cutaneous leishmaniasis necessary. Based on the resultsfound in a controlled, open, randomized, phase III clinical trial, the efficacy and safety of miltefosine was compared to that of thermotherapy for the treatment of cutaneous leishmaniasis in Colombia. Adult patients from the Colombian army participated in the study; they received either 50 mg of miltefosine three times per day for 28 days by the oral route (n = 145) or a thermotherapy (Thermomed®) application of 50 °C for 30 seconds over the lesion and surrounding area (n = 149). Both groups were comparable with respect to their sociodemographic, clinical, and parasitological characteristics. The efficacy of miltefosine by protocol and by intention to treat was 70% (85/122 patients) and 69% (85/145 patients), respectively. The adverse effects were primarily gastrointestinal for miltefosine and pain at the lesion site after treatment for thermotherapy. No statistically significant difference was found in the efficacy analysis (intention to treat and protocol) between the two treatments